Correlates of food insecurity status of urban households in Ibadan metropolis, Oyo state, Nigeria (2018)
Food insecurity is a daily reality for hundreds of millions of people around the world especially in sub-Saharan Africa. In Nigeria, the situation is alarming given the efforts made by independent, successive governments to achieve food security. This persistent food insecurity problem has been found to result mainly from unacceptably high levels of poverty, low priority for nutrition on the agenda of government and resulting poor funding. In addition, the high rate of urbanization in Nigeria has exacerbated the problem of urban food insecurity as urban dwellers contribute to an increasingly important share of the food insecure. In the light of this, the correlates of food insecurity of households in Ibadan Metropolis were examined using data collected from 150 representative households. Data obtained were analyzed employing descriptive statistics, food security index and the probit model. The estimated food insecurity line was 1948.82. Based on this, 29.3 percent of the households were classified as food insecure while 70.7 percent were classified as food secure. Econometric analysis revealed that asset ownership, tertiary educational status of the household head, household size and employment status of the household head were among the major determinants of household food insecurity in the study area. Efforts at improving urban food security should therefore take these factors into account. This could be through the targeting of vulnerable households for social protection measures that would strengthen their asset base among other measures.